The Influence of Content Marketing and Live Streaming on Impulse Buying of the Jiniso Brand on TikTok Shop (A Case Study of Generation Z in Gorontalo City) - Risnawaty Suleman; Rizan Machmud; Yulinda L Ismail; Melan Angriani Asnawi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine: (1) the effect of content marketing on impulse buying of the Jiniso brand in TikTok Shop, (2) the effect of live streaming on impulse buying of the Jiniso brand in TikTok Shop, and (3) the effect of content marketing and live streaming on impulse buying. This study used a quantitative approach by distributing questionnaires to 100 respondents who are Generation Z in Gorontalo City. The sampling technique used purposive sampling. Data were analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that: (1) partially, content marketing has a positive and significant effect on impulse buying with a significance value of 0.042 and a calculated t > t table, namely 2.968 > 1.948, (2) live streaming also has a positive and significant effect on impulse buying with a significance value of 0.000 and a calculated t > t table, namely 5.062 > 1.948; and (3) simultaneously, content marketing and live streaming have a significant effect on impulse buying with a significance value of 0.000 and f count > f table, namely 33.701 > 3.09. The coefficient of determination (R²) value of 0.604 indicates that 60.4% of the variation in impulse buying can be explained by content marketing and live streaming, while 39.6% is influenced by other variables not examined in this study.